Endophytic fungi: nature’s solution for antimicrobial resistance and sustainable agriculture - Nazir, Asiya; Puthuveettil, Abdul R.; Hussain, Fathima Hasnain Nadeem; Hamed, Khalid E.; Munawar, Nayla (Frontiers in Microbiology, 2024)
The growing threat of antimicrobial resistance (AMR) has underlined the need for a sustained supply of novel antimicrobial agents. Endophyte microorganism that reside within plant tissues as symbionts have been the source of potential antimicrobial substances. However, many novel and potent antimicrobials are yet to be discovered from these endophytes. The present study investigates the potential of endophytic fungi as a source of novel bioactive chemicals with antibacterial capabilities. These fungi synthesize secondary metabolites such as polyketides and peptides via polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) pathways. Notable substances, like prenylated indole alkaloids and fumaric acid, have shown promising antibacterial and antifungal properties against multidrug-resistant infectious agents. This review also emphasizes the symbiotic link between endophytes and their host plants, which is critical for secondary metabolite production. The study focuses on the significance of isolation methods for endophytes and proposes their use in for sustainable agriculture, bioremediation, and medicine. Future research combining endophytic biodiversity analysis with next-generation sequencing (NGS) and nanotechnology could provide novel techniques for combating AMR and contributing to sustainability across multiple industries.